Robinson Crusoe - De Graaf, Anne; Ruyer, Franc?ois; Defoe, Daniel 1661?-1731. (Makati City St. Pauls, 1997)
As the sole survivor of a shipwreck, an Englishman lives for nearly thirty years on a deserted island.
"Original ed. published in Denmark by Sacandinavia Pub. House., Copenhagen, Denmark."
Keywords: Crusoe, Robinson (Fictitious character) -- Juvenile fiction; Survival after airplane accidents, shipwrecks, etc. -- Juvenile fiction; Shipwrecks -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction